2003
DOI: 10.1093/ps/82.6.1024
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble phosphorus in fresh broiler litter is dependent upon phosphorus concentration fed but not on fungal phytase supplementation

Abstract: This experiment determined the effects of different phosphorus (P) feeding programs on total and water-soluble P excretion by broilers. Ross 308, male broilers were fed an industry (IND) diet (0.48, 0.35, 0.31, and 0.30% nonphytate P; NPP), an industry diet with reduced NPP and supplemental phytase [IND + PT; 600 phytase units (FTU)/kg; 0.36, 0.26, 0.20, and 0.19% NPP], a diet to more closely meet the birds' NPP requirements in which NPP was reduced further with supplemental phytase (REQ + P; 600 FTU/kg; 0.36,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
25
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 8 publications
10
25
1
2
Order By: Relevance
“…), feed is supplemented with mineral P to ensure birds absorb sufficient quantities of P. However, P is inefficiently utilized by birds, with about 30% of ingested P utilized [18]. The remaining P (~70%) passes though the bird's digestive tract and is excreted [19].…”
Section: Nomentioning
confidence: 99%
“…), feed is supplemented with mineral P to ensure birds absorb sufficient quantities of P. However, P is inefficiently utilized by birds, with about 30% of ingested P utilized [18]. The remaining P (~70%) passes though the bird's digestive tract and is excreted [19].…”
Section: Nomentioning
confidence: 99%
“…DeLaune et al (2001) reported increased soluble phosphorus runoff from the litter of broilers given dietary phytase. However, Applegate et al (2003) reported that watersoluble phosphorus concentrations in broiler litter were not affected by the concentration of phosphorus given, relative to bird requirements, when phytase was added to the diet. More research is needed on calcium and phosphorus requirements of market age turkeys to ensure that phytase is used properly to help reduce the water-soluble phosphorus content of the litter while maintaining growth performance and bone integrity.…”
Section: Discussionmentioning
confidence: 98%
“…It is noteworthy that dietary total P concentrations were lower in the study of Applegate et al (2003). The ecological benefits of phytase supplemented broiler diets, formulated to reduced non-phytate-P specifications, coupled with minimal increases in litter moisture during storage were emphasised by McGrath et al (2005).…”
Section: Effect Of Exogenous Enzyme Supplementation On the Overall Pementioning
confidence: 97%
“…For example, Miles et al (2003) reported that while phytase supplementation of maize-soy diets reduced total P in broiler litter, levels of soluble P were increased (2.85 g kg −1 versus 2.17 g kg −1 ). In contrast, however, Applegate et al (2003) compared standard maize-soy broiler diet with three different phytase-supplemented diets. Overall, phytase reduced total P in fresh litter by 32.2% (7.55 g kg −1…”
Section: Effect Of Exogenous Enzyme Supplementation On the Overall Pementioning
confidence: 99%